The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1111/j.1476-5381.1987.tb10290.x
|View full text |Cite
|
Sign up to set email alerts
|

Blockade by nifedipine of responses to intravenous bolus injection or infusion of α1‐and α2‐adrenoceptor agonists in the pithed rat

Abstract: 1 Nifedipine was tested against pressor responses in the pithed rat to ten agonists with varying selectivity for a,-and a2-adrenoceptors, injected as a bolus or infused intravenously: i.e. amidephrine, azepexole, cirazoline, indanidine, M7, methoxamine, noradrenaline (NA), oxymetazoline, phenylephrine and xylazine. Nifedipine, administered before the agonists, inhibited responses initiated by all agonists, usually for both the bolus and infusion responses. 2 With a bolus, blockade was significantly greater aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

1988
1988
2000
2000

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 15 publications
1
12
1
Order By: Relevance
“…It has been suggested previously that 2-rather than a1-adrenoceptor activation is more effective in maintaining the compensatory vasoconstriction to haemorrhage over long periods of time (Bond & Johnson, 1985). This theory is in accord with the observation that, in pithed rats, the pressor responses to infusions of a2-adrenoceptor agonists are maintained for longer than those to infusions of x1-adrenoceptor agonists (McGrath & O'Brien, 1987). It is interesting to note, however, that in the present study, haemorrhage potentiated the pressor response to the amidephrine infusion, whilst it depressed the response to the infusion of B-HT 933.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It has been suggested previously that 2-rather than a1-adrenoceptor activation is more effective in maintaining the compensatory vasoconstriction to haemorrhage over long periods of time (Bond & Johnson, 1985). This theory is in accord with the observation that, in pithed rats, the pressor responses to infusions of a2-adrenoceptor agonists are maintained for longer than those to infusions of x1-adrenoceptor agonists (McGrath & O'Brien, 1987). It is interesting to note, however, that in the present study, haemorrhage potentiated the pressor response to the amidephrine infusion, whilst it depressed the response to the infusion of B-HT 933.…”
Section: Discussionsupporting
confidence: 92%
“…The pressor response to amidephrine, as with other ao-adrenoceptor agonists is biphasic (McGrath & O'Brien, 1987), with an initial peak pressor phase followed by a lower, though more sustained, secondary pressor response during which the microspheres were injected. For the normotensive and haemorrhagic, hypotensive saline control groups, an initial bolus of 0.2ml saline was followed by a second 0.2ml bolus and the microsphere injection was given during an 0.1 ml min1 infusion of saline (these are referred to as the saline/saline and haemorrhage/saline groups).…”
Section: Determination Ofcardiac Output and Its Distributionmentioning
confidence: 99%
“…a-Adrenoceptor-mediated pressor responses to circulating agonists are partly affected by Ca2+ antagonists such as nifedipine (Timmermans et al, 1983), but this varies with the agonist and method of administration and is partly attributable to the duration of the response (McGrath & O'Brien, 1987). With sympathetic nerve-mediated responses in different preparations, any variability in blockade is likely to be at least partly attributable both to variations in the contributions from purinergic and adrenergic transmission and to the duration of the stimulus and/or the response.…”
Section: Discussionmentioning
confidence: 99%
“…pressor responses to exogenous noradrenaline (NA) or other agonists: the initial, early, rapid responses are resistant but the late components or responses to infusion are blocked McGrath & O'Brien, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Since their discovery it has been suggested that a number of factors can differentially modulate responses to a-adrenoceptor agonists, such as blood pH and blood gases (McGrath et al, 1982;Grant et al, 1985), calcium channel blockers (CCBs) or angiotensin converting enzyme (ACE) inhibitors Timmermans et al, 1982). It was initially suggested that x2-adrenoceptor-mediated responses were more susceptible to the action of CCBs and ACE inhibitors than were equivalent sized al-adrenoceptor-mediated responses de Jonge et al, 1982;Timmermans et al, 1982), although there is now evidence that both CCBs and ACE inhibitors preferentially inhibit the late phase of the pressor response to a bolus injection of an agonist, irrespective of subtype specificity McGrath & O'Brien, 1987). The study of modulatory influences on responses mediated via different adrenoceptor subtypes in models such as the pithed rat is limited, however, by a number of factors.…”
Section: Introductionmentioning
confidence: 99%